Surveillance nursing diagnoses, ongoing assessment and outcomes on in-patients who suffered a cardiorespiratory arrest - Maria-Eulàli; Núria Fabrellas-Padrés; Jordi Adamuz-Tomás; Sònia Cadenas-González; Maribel Gonzalez-Samartino; Laura de la Cueva Ariza; Pilar Delgado-Hito (SciELO, 2018)
ABSTRACT Objective The purposes of this study were to examine the frequency of surveillance-oriented nursing diagnoses and interventions documented in the electronic care plans of patients who experienced a cardiac arrest during hospitalization, and to observe whether differences exist in terms of patients' profiles, surveillance measurements and outcomes. Method A descriptive, observational, retrospective, cross-sectional design, randomly including data from electronic documentation of patients who experienced a cardiac arrest during hospitalization in any of the 107 adult wards of eight acute care facilities. Descriptive statistics were used for data analysis. Two-tailed p-values are reported. Results Almost 60% of the analyzed patients' e-charts had surveillance nursing diagnoses charted in the electronic care plans. Significant differences were found for patients who had these diagnoses documented and those who had not in terms of frequency of vital signs measurements and final outcomes. Conclusion Surveillance nursing diagnoses may play a significant role in preventing acute deterioration of adult in-patients in the acute care setting.